Α-Mangostin Induces Apoptosis in Human Osteosarcoma Cells Through ROS-Mediated Endoplasmic Reticulum Stress via the WNT Pathway. (23rd July 2021) - Yang, Shengsen; Zhou, Fei; Dong, Yi; Ren, Fei
Α-mangostin has been confirmed to promote the apoptosis of MG-63 cells, but its specific pro-apoptosis mechanism in osteosarcoma (OS) remains further investigation. Here, we demonstrated that α-mangostin restrained the viability of OS cells (143B and Saos-2), but had little effect on the growth of normal human osteoblast. α-mangostin increased OS cell apoptosis by activating the caspase-3/8 cascade. Besides, α-mangostin induced endoplasmic reticulum (ER) stress and restrained the Wnt/β-catenin pathway activity. 4PBA (an ER stress inhibitor) or LiCl (an effective Wnt activator) treatment effectively hindered α-mangostin-induced apoptosis and the caspase-3/8 cascade. Furthermore, we also found that α-mangostin induced ER stress by promoting ROS production. And ER stress-mediated apoptosis caused by ROS accumulation depended on the inactivation of Wnt/β-catenin pathway. In addition, α-mangostin significantly hindered the growth of xenograft tumors, induced the expression of ER stress marker proteins and activation of the caspase-3/8 cascade, and restrained the Wnt/β-catenin signaling in vivo. In short, ROS-mediated ER stress was involved in α-mangostin triggered apoptosis, which might depended on Wnt/β-catenin signaling inactivation.